PERBANDINGAN ANALISIS GEMPA STATIK EKIVALEN KELAS SITUS TANAH KHUSUS DENGAN KELAS SITUS TANAH LUNAK BERDASARKAN SNI 1726-2019 - Halimatusadiyah, Halimatusadiyah; Srihandayani, Susy; Desriyati, Welly (Universitas Muhammadiyah Palembang, 2022)
One of the factors that influence planning of earthquake-resistant building structures is condition of the soil layer and analysis structure. This research discusses about the analysis of static equivalent earthquake to site class F (SF) compare with site class E (SE) based on SNI 1726-2019. For site class F (SF) using the design response spectrum with the design response spectral acceleration for each period not to take more than 80% of the spectral acceleration value specified for the site class E, and then analyzed with using a dynamic response spectrum analysis method at the location of site class F or identified as site class F with the fulfillment requirements as site class F, has the potential for liquefaction. While for site class E (SE) uses the parameters be appointed by SNI 1726-2019. This study aims to compare the increase in earthquake load from static equivalent that occurs in site class F and site class E. The results of the static equivalent analysis show that the value of seismic base shear for site class E (SE) is 14687,085 kN, and site class F (SF) is 16155.793 kN has increased by 10.3%, this affects the calculation of the equivalent lateral force on each floor of the building structure